WINTER WHEAT BREEDING IN ALTAY - V. A. Boradulina (Зерновое хозяйство России, 2018)
Soft spring wheat is the main grain crop in Altay and it occupies more than 2 mln hectare. In 2015 the harvesting area of winter wheat was about 84000 ha, which was 4% less than that of spring wheat. Being highly vulnerable to Siberian winter the crop has limited distribution and grows well in the areas with good and steady reserves of snow. With good overwintering the productivity of winter wheat exceeds the productivity of spring wheat by 1,5-2 times. At present two varieties ‘Zhatva Altaya’ and ‘Zimushka’ developed in Altay RIA are introduced into the Register of the varieties approved for use in the West-Siberia region and the variety ‘Metelitsa’ is in the process of State Variety Testing. For the conditions of Siberia frost tolerance as the principal component of winter tolerance is the most essential property of the crop. The study of the varieties developed by All-Russian RIGC named after I.G. Kalinenko (town of Zernograd, Rostov region) in different conditions allowed finding the sources of useful properties. All varieties of ARRIGC are stable to lodging, they form large grain and with good overwintering they give the same or better productivity as the Siberian varieties. But in the hard conditions only the varieties ‘Izyuminka’ and ‘Stanichnaya’ showed the same productivity as the variety ‘Zhatva Altaya’. Such varieties as ‘Asket’, ‘Stanichnaya’, ‘Pamyati Kalinenko’, ‘Izyuminka’, ‘Dar Zernograda’ have been introduced in the program of hybridization of winter wheat genotypes for the conditions of Siberia.